Razvoj populacij divjadi in njihovega življenjskega okolja v severnozahodni Sloveniji - Koren, Iztok (Gozdarski vestnik, 2009)
The work explores the development of wild game populations in the periods 1951-1960 and 1994-2003 in the Tolmin forest management area in the North-westof Slovenia. The two periods are not similar with regard to the species composition of the game. The two periods are similar or dissimilar according to the presence of specific wild game species. Between the two periods the uses of space changed a lot, the proportion of farmland was reduced while the proportion of forest increased. The change of use of space has a great impact on the number and distribution of wild game populations.
Keywords: raba prostora; divjad; populacije; lov; Slovenia; Slovenija